Aplikasi Virtual Tour Berbasis Web untuk Informasi Tata Letak Gedung Sekolah Menggunakan MDLC - Ayu Latifah; Bintang Nur Alfiyah (Institut Teknologi Garut, 2026)
Virtual tour is an interactive multimedia technology that allows users to explore a location digitally through 360° panoramic visualization. Currently, SMK Negeri 9 Garut still relies on conventional media such as brochures and banners to convey building layout information, which limits its ability to provide an optimal interactive experience. This study aims to design and develop a web-based virtual tour that can be accessed broadly and efficiently. The method used is the Multimedia Development Life Cycle (MDLC), consisting of the concept, design, material collecting, assembly, testing, and distribution stages. Research data were obtained through observation, interviews, and documentation, then processed using 3DVista software to produce 360° panoramas, hotspots, text information, and audio. Black-box testing results indicate that all application features function as intended. From a software engineering perspective, this study underscores the implementation of the Multimedia Development Life Cycle (MDLC) as a systematic approach for developing interactive multimedia systems within educational environments. This implementation not only results in an optimally functioning application but also demonstrates the effectiveness of MDLC in designing web-based solutions that support the interactive and informative delivery of educational content.